THE PENALTY CLAUSE DOCTRINE: UNLOVABLE BUT UNTOUCHABLE. (14th March 2016) - Morgan, Jonathan
Abstract : BARRY Beavis fought the law of contract and the law won. To the disappointment of motorists nationwide, he failed to show that an £85 shopping centre parking fine was an unenforceable penalty at common law (or under the Unfair Terms in Consumer Contracts Regulations 1999). Ironically, he lends his name notwithstanding to a leading case which confirmed the existence of the penalty doctrine (a joined commercial challenge also failed on the facts): ParkingEye Ltd. v Beavis; Cavendish Square Holding v El Makdessi [2015] UKSC 67; [2015] 3 W.L.R. 1373.